Diabetes Mellitus II: the importance of support networks to support the suffering - Cartas Fuentevilla, Guadalupe (2011)
Objective. To understand the key role played by the family, institutional, and friends support in the diabetes education program dedicated to the women at the Health Center and the Diabetes Club of San Cristobal de Las Casas, Chiapas, through the process health-illness-treatment of the diabetes mellitus II. Metodology. Ethnographic cualitative study: the data were obtained making careful interviews to four diabetic women. Results. Institutional programs constitute the main strategy for attention and control for diabetic supplies.Women see more valued in the Club that within your household because they feel identified and understood by the other sick generating a process identity on the condition of diabetes. Although most of the cases the family constitutes an invaluable support , there exist cases in which the family may represent a complication in the process of control and relief; in such cases the friends can supply the support required. Conclusions. The network stronger and more institutional support is because through this they have learned to re-learn your condition, a new meaning through a process of compromise between the discourse of the biomedicine and the common-sense knowledge shared to each other by others and other ill. Through the Health center, especifically , the Diabetes Club of San Cristobal, the institutional medicine has generated trust and warmth in doctor patient in order to motivate relationship (institutional medicine, through the Health Center and, especially, the Diabetes Club of San Cristobal de Las Casas, it has managed to generate trust and warmth in the doctor-patient relationship in order to motivate the appropriate control, relief and the final recovery, control and relief of their suffering.